Investment Strategy For The Development Of Fisheries Sector In Indonesia: An Application A Dynamics Regional Economics Allocation Model (Dream) - Tridoyo Kusumastanto (Buletin Ekonomi Perikanan, 1996)
The purpose of this researh is to develop a national investment policy planning model for the Indonesian fisheries sector. The specific objective is to estabilish a develompent strategy for the fisheries sector, with specific attention results from the proposed study will be useful in providing policy directions and indicating magnitude of the investment required for efficient planning of the sector.